2009
DOI: 10.1016/j.neuroimage.2008.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between glioblastomas and solitary brain metastases using diffusion tensor imaging

Abstract: The purpose of this study is to determine whether diffusion tensor imaging (DTI) metrics including tensor shape measures such as linear and planar anisotropy coefficients (CL and CP) can help differentiate glioblastomas from solitary brain metastases. Sixty-three patients with histopathologic diagnosis of glioblastomas (22 men, 16 women, mean age 58.4 years) and brain metastases (13 men, 12 women, mean age 56.3 years) were included in this study. Contrast-enhanced T1-weighted, fluid attenuated inversion recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
113
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 147 publications
(127 citation statements)
references
References 37 publications
13
113
1
Order By: Relevance
“…15,[25][26][27] We speculate that these hyperintensities may represent tumor parts with focal high cellularity. 13 On visual inspection, the perilesional hyperintense FA rim is the most sensitive, specific, and accurate sign in differentiating TDLs from high-grade gliomas. The lower incidence of a hyperintense FA rim associated with TDLs was concurrently supported by quantitative analysis finding that perilesional FA values were significantly lower in TDLs than in high-grade gliomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,[25][26][27] We speculate that these hyperintensities may represent tumor parts with focal high cellularity. 13 On visual inspection, the perilesional hyperintense FA rim is the most sensitive, specific, and accurate sign in differentiating TDLs from high-grade gliomas. The lower incidence of a hyperintense FA rim associated with TDLs was concurrently supported by quantitative analysis finding that perilesional FA values were significantly lower in TDLs than in high-grade gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…Malhotra et al 11 found peripheral restricted diffusion on DWI in 11 of 18 patients with TDLs, while Masu et al 12 observed that intralesional fibers appeared to be a pyramidal tract on diffusion tractography in a patient with TDL. Conversely, the perilesional hyperintense FA rim that is frequently found in the perifocal edema of high-grade gliomas 13 has not been described in TDLs. We aimed to differentiate TDLs from highgrade gliomas with DTI because the contributory role of DTI in differentiating TDLs from high-grade gliomas is not clear and quantitative comparison between the 2 has not been reported, to our knowledge.…”
mentioning
confidence: 91%
“…Wang et al (18) investigated the application of a combination of scalar DTI parameters for the classification of solitary GBM and MET tumours, and achieved an area under receiver operating characteristic (ROC) curve (AUC) of 0.98. However, Wang et al (18) delineated several ROIs both inside and outside the tumour core, which potentially provides a subjectivity that may reduce experimental reproducibility.…”
mentioning
confidence: 99%
“…However, Wang et al (18) delineated several ROIs both inside and outside the tumour core, which potentially provides a subjectivity that may reduce experimental reproducibility.…”
mentioning
confidence: 99%
“…In contrast, another study reported that glioblastomas have higher FA in the enhancing regions than metastases. 12 The potential reasons for these conflicting results may include differ-ences in analysis methods, particularly in defining the region of interest, as well as the relatively small size of cohorts used in individual studies (n ϭ 24 -66). 4,5,7,10,13 Hence, a primary objective of this study was to investigate the DTI characteristics of glioblastomas and brain metastases in a substantially larger cohort of patients, in order to determine whether they may have diagnostic utility.…”
mentioning
confidence: 99%